The Introduction To Ibn Abidin's “Radd Al-Muhtar” - Tursunov Mukhiddin Davudovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article provides information about the introduction to Ibn Abidin’s "Radd al-Muhtar," one of the eminent scholars of the Hanafi school of thought. The article also covers the origins, development, and spread of the Hanafi school, along with details about its prominent scholars and the methods they used in acquiring knowledge.